The evolution of biblical Hebrew linguistics in South Africa the last 60 years - Naudé, Jacobus A.; Miller, Cynthia L. 1957- (2018)
In this article we survey the evolution of Biblical Hebrew linguistics in South Africa during the last six decadesits dependence upon and contribution to European and American developments and its distinct contributions to the field. Three eras can be distinguished. In the first era, the study of Biblical Hebrew in South Africa was primarily philological in nature and both teaching grammars and research focused mainly on grammar and specifically the writing system, word formation and vocabulary. In the second era, the study of Biblical Hebrew in South Africa was heavily influenced by the new developments in Europe and the USA concerning linguistics and especially its influence in the fields of Biblical Hebrew syntax and discourse analysis. In the third era, Biblical Hebrew linguistics in South Africa contributes to the development of the field by taking into account the complexity of Biblical Hebrew as a language. The description and explanation of the nature of the verbless clause, and specifically the tripartite and left dislocated verbless clause in Biblical Hebrew are discussed as a case in point both of the development of linguistics and Biblical Hebrew in South Africa and of the impact of linguistics on exegesis and Bible translation.